Abundance and diversity of small mammals in Swedish beaver systems - Glabischnig, Felicitas (SLU/Dept. of Aquatic Sciences and Assessment, 2015)
Through their ecosystem engineering activities, beavers (Castor fiber ) create ponds and riparian zones littered with deadwood, providing hetero- geneous micro-habitats for a variety of small mammal species. In this study small mammals were snap-trapped in nine beaver systems and four reference wetland systems that were not created by beavers in southern and central Sweden to compare abundance and diversity of voles, shrews and mice. In addition, structural habitat factors were recorded at the study sites. Beaver sites had high amounts of coarse and fine woody debris and standing dead- wood. A principal component analysis of the structural habitat factors showed that over a third of the variation in the data can be explained by the degree of influence that C. fiber has on the system. Abundance and true diversity (expH’ ) of small mammals were positively correlated with the amount of deadwood in the systems. Bank voles (Myodes glareolus ) were shown to have no preference for either beaver or non-beaver wetlands, but subadult bank voles had higher mean weights in newly colonized beaver systems with extensive grass layers than in recolonized systems. It has been concluded that beavers are indeed creating habitat conditions that are favourable for small mammal diversity and abundance, especially as far as shrews and mice are concerned.